An estimation of bamboo borer biomass in Son La province, northwestern Vietnam and remarks on its parasitic characteristics - Mai, Pham Quynh (Vietnam Journal of Science and Technology, 2016)
Vietnam’s population has been increasing, will reach 100 million peoples in the near future. When the population increased, the amount of food from traditional sources can not afford. The study of insects as food supplement in this period is very necessary. The bamboo larvae of Omphisa fuscidentalis are used as food by local peoples in mountainous provinces in Northern Vietnam in the long time. The larvae are also used as good to purchase on the domestic market today. In this paper, we presented the results of studies on the infested rates of bamboo larvae on different bamboo species and some characteristics in their parasitic larval stage and estimated reserves of the larvae in the province of Son La.